PENERAPAN STUDENT TEAM ACHIEVEMENT DIVISION DALAM KEMAMPUAN MENULIS TEKS DRAMA - Simatupang, Linsa; Syahfitri, Dian (Universitas Pendidikan Ganesha, 2019)
His study was conducted to find out whether the Student Team Achievement Division model had a significant influence on the ability to write drama text of students in eighth grade Medan Agung Budi Middle School. The design of this study was carried out by classroom action research. The research subjects were 32 students. Instruments in collecting data are interviews, observation, tests, and documentation. The data collected was analyzed by qualitative descriptive analysis. The procedure of this study uses a class action research design, namely the stages of planning, implementation, observation and reflection. The results of this study indicate that students' ability to write drama texts has increased. After the implementation of two cycles, the first cycle is 56.25% and in the second cycle, 78.12%.